Cancer risk in 892 089 patients with psoriasis in Korea: A nationwide population‐based cohort study. Issue 2 (16th November 2018) - Lee, Ji Hyun; Kim, Hyo Jung; Han, Kyung Do; Kim, Ha‐Na; Park, Young Min; Lee, Jun Young; Park, Yong‐Gyu; Lee, Young Bok
Abstract: The relationship between psoriasis and cancer has not yet been established. The aim of this study was to evaluate the association of psoriasis with certain cancers using national statistics. All patients with psoriasis ( n  = 892 089; 51.7% male) and age‐ and sex‐matched control subjects ( n  = 4 460 445) at a 5:1 ratio were enrolled using data from the National Health Insurance Service between 2007 and 2014 in Korea. In psoriatic subjects, overall cancer risk was higher than for subjects without psoriasis after adjusting for income level, diabetes, hypertension, dyslipidemia and place of residence (hazard ratio, 1.065; 95% CI, 1.049–1.081). The risk of cancer increased in the following order: prostate, thyroid, liver, ovarian, lung, leukemia, skin, multiple myeloma, lymphoma and testicular. The severity and sex of psoriatic patients also had different cancer risks. In psoriatic patients, a slightly increased risk for specific malignant neoplasms was shown. Therefore, periodic screening for cancer risk is recommended in patients with psoriasis.